PREDICTING THE COMPRESSIVE STRENGTH OF PBA – CLAY REFRACTORY BRICKS USING RESPONSE SURFACE METHOD - C., Chijioke; P., Okoye; W. E., Igwegbe; J.C., Ugwuegbulam (International Journal of Research -GRANTHAALAYAH, 2018)
The importation of refractory materials is one of the biggest challenges industries faced in third world countries, of which Nigerian is one of them. The addition of palm bunch ash to clay in the production of clay bricks is one of the ways refractory materials are produced. The clay used here was Nsu clay. This work looked at the compressive strength of refractory bricks which is one of the properties of refractory materials. The work eliminates the traditional methods of trial and error and the rigorous mathematical analysis associated with the formation of some regression models in the prediction of some properties of refractory bricks. This was achieved by the use of Surface Response method. A regression model to predict the strength of a refractory brick was formulated, the model was found to be adequate based of the analysis of variance in which the Rsq, Rsq (adjusted) and Rsq (prediction) were found to be adequate, hence the model can be used to predict the compressive strength of refractory bricks. The optimal compressive strength was found to be 30.1513KN/m2 at a ratio of 1:0.2570 at a water/clay ratio of 4.2590. Also, from the results it can be seen that the compressive strength of bricks decrease with increase in the percentages of palm bunch ash.